The great Gatsby - Fitzgerald, F. Scott (Francis Scott), 1896-1940.; Prigozy, Ruth. (Oxford : Oxford University Press, 2008)
A portrayal of the power of romantic imagination, as well as the pathos and courage entailed in the pursuit of an unattainable dream, 'The Great Gatsby' is a classic fiction of hope and disillusion, that encapsulates the spirit of the 'Jazz Age'.
Keywords: First loves -- Fiction; Rich people -- New York (State) -- New York -- Fiction; Classics